Calculation Analysis of Steam Consumption Efficiency on The Dryer Section in Paper Machine - Abdillah Taqiyuddin; Ridwan Abdurrahman (Proksima, 2023)
This research aims to analyze the efficiency of steam consumption in the Dryer Section at the Paper Machine. The research method involves calculating the actual steam consumption efficiency and comparing it with the TAPPI efficiency standard. The research results show that the average steam consumption efficiency for grade W/FIPF35-70 reached 94.51%, exceeding the TAPPI standard of 86%. However, some observations indicate substandard results, which can be caused by factors such as raw material quality, process settings, and equipment wear. The conclusions of this research provide insight into the factors that influence steam consumption efficiency, providing a basis for improving performance in Dryer Section Paper Machine.